Entanglement Dynamics of Two Qubits Coupled Independently to Cavities in the Ultrastrong Coupling Regime: Analytical Results*Supported by the National Natural Science Foundation of China under Grant Nos 11174254 and 11474256. (May 2016) - Zhu 朱, Wei-Ting 维婷; Ren 任, Qing-Bao 清褒; Duan 段, Li-Wei 立伟; Chen 陈, Qing-Hu 庆虎
Abstract : Dynamics of quantum entanglement of two qubits in two identical quantum Rabi models is studied analytically in the framework of corrections to the rotating-wave approximations. A closed-form expression for the entanglement dynamics initiated from the well-known Bell states is derived, which is very close to the numerical exact results up to the ultrastrong coupling regime. It is found that the vanishing entanglement can be purely induced by the counter-rotating terms, and can be enhanced with the atom–cavity coupling.